College students’ psychology and behavior in the context of online public opinion: a cross-sectional study in Jiangsu Province, China - Chen, Xiaoqing; Wu, Qi; Yin, Dehui (Frontiers in Psychology, 2024)
Background: With the rapid development of the Internet and the widespread use of social media, online public opinion has profoundly impacted the psychology and behavior of college students. College students are in a crucial stage of psychological development and self-awareness, making them highly sensitive to online information and easily influenced by online public opinion. Methods: This study employed a cross-sectional design to explore the psychological adaptation and behavioral responses of college students to online public opinion. Data were collected from a convenience sample of 2,294 college students across four universities in Xuzhou City, Jiangsu Province, using an online questionnaire administered via Questionnaire Star. The study utilized three well-established scales: the Belief in a Just World (BJW) Scale, the Connor-Davidson Resilience Scale (CD-RISC), and the Internet Altruistic Behavior (IAB) Scale. Statistical analyses were conducted using SPSS 26.0, encompassing descriptive statistics, independent samples t-tests, ANOVA, correlation analysis, and multiple linear regression analysis, with a significance level set at P < 0.05. Any responses with missing or inconsistent data were excluded from the analysis, ensuring a final effective response rate of 95.7%.Results: Among the 2,294 participants, 60.1% were female, 56.8% were from rural areas, and 57.4% were non-only children. Univariate analysis showed significant relationships between BJW scores and gender, family economic status, parents' attitudes, relationships with classmates, and emotional responses to negative online content(P<0.001). CD-RISC scores were significantly related to only child status, family economic status, parents' attitudes, relationships with classmates, and emotional responses to negative online content(P<0.05). IAB scores were significantly related to gender, grade level, family economic status, parents' attitudes, relationships with classmates, and emotional responses to negative online content(P<0.05). Correlation analysis revealed significant associations among BJW, CD-RISC, and IAB. Multiple regression analysis identified key predictors for each scale, including gender, parents' attitudes, relationships with classmates, emotional responses to negative online content, and various other factors(P<0.001).In the context of online public opinion, targeted interventions by families and schools are needed to regulate the psychological and behavioral states of college students, promoting good mental health and positive behavior in the complex online environment.